D-Dimer Is a Diagnostic Biomarker of Abdominal Aortic Aneurysm in Patients With Peripheral Artery Disease - Cai, Huoying; Pan, Baihong; Xu, Jie; Liu, Shuai; Wang, Lei; Wu, Kemin; Yang, Pu; Huang, Jianhua; Wang, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background Etiology and risk factors of peripheral artery disease (PAD) include age, smoking, and hypertension, etc. , which are shared by an abdominal aortic aneurysm (AAA). Concomitance with AAA in patients with PAD is not rare but is easily overlooked in the clinical situation, though management strategies are altered totally. This study aims to investigate diagnostic biomarkers for the prediction of AAA in patients with PAD. Methods A total of 684 patients diagnosed with AAA and/or PAD were enrolled and analyzed retrospectively. Each patient with PAD and AAA was gender and age-matched. Demographic data, medical history, and serum laboratory test profiles were obtained. Statistical analysis was performed to determine diagnostic biomarkers of AAA in patients with PAD. Results Firstly, 320 patients with PAD-only and 320 patients with AAA-only were compared. Levels of bilirubin and D-Dimer were decreased, while the incidence of diabetes mellitus, levels of fibrinogen, and platelet count were increased significantly in patients with PAD-only compared with those in patients with AAA-only (P < 0.001). Next, 364 patients with PAD (44 patients with AAA) and 364 patients with AAA (44 patients with PAD) were compared. Multivariate logistic regression analysis confirmed the differential distribution of bilirubin, D-dimer, fibrinogen, and platelet count between patients with AAA and patients with PAD (P < 0.05). Receiver operator curves (ROC) showed that the area under the curve (AUC) of total bilirubin, direct bilirubin, D-dimer, fibrinogen, and platelet count was 0.6113, 0.5849, 0.7034, 0.6473, and 0.6785, respectively. Finally, to further validate the predictive efficacy of mentioned markers, a multivariable logistics regression analysis was performed between the PAD only group and the PAD with AAA group. The results suggested increased levels of D-dimer in the PAD with AAA group compared to the PAD only group (OR: 2.630, 95% CI:1.639–4.221; P < 0.001). In particular, the Youden index suggested that the cut-off value of D-dimer for predicting AAA in patients with PAD was 0.675 mg/L with a sensitivity of 76.9% and a specificity of 84.9% (AUC = 0.8673; 95% CI, 0.8106–0.9240, P < 0.001). In all 364 patients with PAD, 41.46% patients were diagnosed AAA when D-dimer is >0.675 mg/L, while only 3.55% patients were diagnosed AAA when D-dimer ≤ 0.675 mg/L. Conclusions PAD and AAA exert different clinical and serum profiles; D-dimer (>0.675 mg/L) is a reliable biomarker for the prediction of AAA in patients with PAD.